2018
DOI: 10.2135/cropsci2017.09.0591
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotinia Blight Resistance in the US Peanut Mini‐Core Collection

Abstract: Germplasm collections are valuable sources of desirable traits such as disease resistance, but many accessions have yet to be characterized. Seventy‐one accessions of the US peanut (Arachis hypogaea L.) mini‐core were evaluated from 2013 to 2015 for yield, seed quality characteristics, Sclerotinia blight (caused by Sclerotinia minor Jagger) resistance in the field, and for a Sclerotinia resistance marker. Twenty‐one accessions with <10% and six accessions with <5% disease incidence were identified from the 2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Stronger correlations exist for the extremes of susceptibility or resistance (Figure 2A and 2B), whereas the marker is less likely to accurately predict phenotypic reactions in the moderate range (denoted by red ovals, Figure 2). These results are similar to those reported previously by others using this marker to screen other germplasm collections Chamberlin, 2014;Bennett et al, 2018;Chamberlin and Puppala, 2018).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Stronger correlations exist for the extremes of susceptibility or resistance (Figure 2A and 2B), whereas the marker is less likely to accurately predict phenotypic reactions in the moderate range (denoted by red ovals, Figure 2). These results are similar to those reported previously by others using this marker to screen other germplasm collections Chamberlin, 2014;Bennett et al, 2018;Chamberlin and Puppala, 2018).…”
Section: Resultssupporting
confidence: 92%
“…Previously, the marker used in this study was shown to be significantly associated with resistance to Sclerotinia blight in peanut cultivars and PIs that had been thoroughly evaluated in field trials (Chenault et al, 2009). The marker has been used previously to screen numerous germplasm collections Chamberlin, 2014;Chamberlin and Puppala, 2018) and the results obtained have been shown to closely agree with phenotypic reaction to S. minor in field trials (Chenault et al, 2009;Chamberlin et al, 2010;Damicone et al, 2010;Bennett et al, 2018). The results of the current study are similar to those reported when the marker was used to screen other collections, with the marker for resistance being prominent in the fastigiata, vulgaris, and hirsuta botanical types.…”
Section: Resultsmentioning
confidence: 81%
“…Lastly, the following three mini-core accessions with unknown susceptibilities to A. rolfsii were also included: CC068 (PI 493880), CC384 (PI 155107), and CC650 (PI 478819). CC068 and CC650 are resistant to Sclerotinia minor in the field (Bennett et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…resistance because other characteristics such as open canopy structure can create microclimates unfavorable for disease (Blad et al, 1978;Dow et al, 1988;Bailey and Brune, 1997). For example, the cultivar Southwest Runner (Damicone et al, 2010) and several mini-core accessions including CC038, CC068, and CC787 (Bennett et al, 2018) exhibit resistance to Sclerotinia minor in the field but are susceptible when inoculated in the laboratory. While severe outbreaks of A. rolfsii are rare in current peanut production areas of Oklahoma, an inoculated field study of the U.S. mini-core that included three cultivars used here indicated that the A. rolfsii assays may correlate with field results.…”
Section: Audpcmentioning
confidence: 99%
“…For the USDA-NPGS peanut collection, disease phenotyping efforts have focused on the more manageable core (Holbrook et al, 1993) and minicore (Holbrook and Dong, 2005) subsets. To date, all or parts of the core collection have been evaluated for resistance to late leaf spot (Anderson et al, 1993;Holbrook and Anderson, 1995), TSWV (Anderson et al, 1996), Rhizoctonia limb rot ((Franke et al, 1999), peanut root-knot nematode (Holbrook et al, 2000), Sclerotinia blight (Damicone et al, 2010;Bennett et al, 2018), pepper spot (Damicone et al, 2010), and web blotch (Damicone et al, 2010). One notable omission from this list of diseases is southern blight, caused by Athelia rolfsii (Curzi) C.C.…”
mentioning
confidence: 99%